2020
DOI: 10.2141/jpsa.0190073
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on MicroRNAs Involved in the Regulation of Chicken Diseases

Abstract: MicroRNAs (miRNAs) are small, non-coding RNA molecules that inhibit protein translation from target mRNAs. Accumulating evidence suggests that miRNAs can regulate a broad range of biological pathways, including cell differentiation, apoptosis, and carcinogenesis. With the development of miRNAs, the investigation of miRNA functions has emerged as a hot research field. Due to the intensive farming in recent decades, chickens are easily influenced by various pathogen transmissions, and this has resulted in large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Growing evidence has demonstrated that miRNAs play a significant role in avian diseases. For example, miRNAs can regulate avian influenza, Marek’s disease, infectious bursal disease and avian mycoplasmosis ( 14 ). In addition, our previous studies have also highlighted the critical role of miRNAs (such as miR-181a-5p, miR-223 and miR-24) during MG infection ( 13 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has demonstrated that miRNAs play a significant role in avian diseases. For example, miRNAs can regulate avian influenza, Marek’s disease, infectious bursal disease and avian mycoplasmosis ( 14 ). In addition, our previous studies have also highlighted the critical role of miRNAs (such as miR-181a-5p, miR-223 and miR-24) during MG infection ( 13 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%